THE ROLE OF HRD MANAGEMENT IN EMPLOYEE CAREER DEVELOPMENT (CASE STUDY OF PT. SURYA TOTO INDONESIA, TBK. TANGERANG) - Masruri Masruri (CAPITAL: Jurnal Ekonomi dan Manajemen, 2024)
The purpose of writing this work is to describe the role of HRD management in employee career development (Case Study of PT. Surya Toto Indonesia, Tbk. Tangerang). The preparation of the work uses a qualitative approach to explore the effectiveness of HRD management in employee career development, using data analysis techniques Miles and Huberman who revealed the importance of corporate investment in human resource development. The findings show that systematic HRD practices contribute significantly to the individual growth of employees and the overall success of the organization. This research underlines that a structured approach in HRD management facilitates sustainable career development for employees, strengthening their capacities Overall. The result of this work is that PT Surya Toto Indonesia has implemented an HRD strategy to support the professional growth of its employees, with training and development programs tailored to the company's needs. An effective performance appraisal system provides critical feedback for employee growth. Through promotions and position rotation, employees are given the opportunity to develop skills and prepare themselves for greater responsibilities. The company also prioritizes employee welfare with health insurance and pension programs. By investing in employee development, PT. Surya Toto Indonesia creates a balance between organizational goals and employee satisfaction, supporting long-term success.